Serum Electrolyte in Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Acharya, Chandra Prasad; Paudel, Kalpana (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of mortality and morbidity worldwide. Though COPD is mainly a chronic disease, many patients experience exacerbations that are related to worst survival outcome, especially with abnormal serum electrolyte level. The objective of this study was to evaluate serum electrolyte levels among the patients with acute exacerbation of COPD.Methods: Structured questionnaire and patients’ charts were used to collect data. Data was analyzed using Statistical Package for the Social Sciences (SPSS) software version 16.0 and descriptive statistics were used to generate the research findings.Results: The mean age of the patients with Acute exacerbation of COPD was 69.57± 9.765 years. Among 100 patients, (83%) belonged to the age group of 60 years and above, (54%) were male, (74%) were married, (52%) were illiterate and (41%) were engaged in agriculture, (41%) consumed alcohol and (67%) were smokers. Dyspnoea (90%) was the most common symptom. The mean level of sodium and potassium were 133.8±4.830 mEq/L, 3.6±0.533 mmol/L, respectively. Fifty seven percent patients had electrolyte disorder. More than half (51%) had hyponatremia and (40%) had hypokalemia. The average value of pH, PaCO2 and PaO2 are 7.34 ± 0.727, 46.64 ± 9.787 mm Hg and 69.38 ± 9.255 mm Hg respectively. Among them, (18%) were in respiratory failure.Conclusion: This study concluded that hyponatremia and hypokalemia are prevalent electrolyte disorder with AE of COPD patients. Therefore, we recommend routine monitoring of the serum electrolytes for better outcomes of patients.